Pharmaceutical marketing of over-the-counter drugs in the current digital era: A review - Mohamad Saleem Anis; Mohamed Azmi Hassali (Faculty of Pharmacy, Mahidol University, 2022)
Digitization is a current era trend that has permeated various daily activities of individuals and businesses. The acceleration of digital adoption can be seen even more with the onset of the COVID-19 pandemic. As a result, a new pattern of pharmaceutical marketing has been defined in the industry in several terms, most notably pharmaceutical digital marketing (PDM). Undeniably, over-the-counter (OTC) drugs, which are pharmaceuticals sold without a medical prescription, are the most affected drug category by this digital transformation in the pharma industry. The content of this review paper is based on secondary data derived from recent literature and Internet sources. The relevant information from various journal articles, books, reports, and reliable web pages has been presented and discussed. Basically, the main body of the review was divided into two fundamental areas of PDM, with a greater emphasis on the context of OTCdrugs: (1) online pharmacies (e-commerce marketing); (2) promotional advertising. In a nutshell, this review provides valuable insights into the emerging concepts of PDM within the scope of OTC drugs.